2021
DOI: 10.3390/jcm10061291
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal Adipose Tissue—Current Knowledge and Future Opportunities

Abstract: The perirenal adipose tissue (PRAT), a component of visceral adipose tissue, has been recently recognized as an important factor that contributes to the maintenance of the cardiovascular system and kidney homeostasis. PRAT is a complex microenvironment consisting of a mixture of white adipocytes and dormant and active brown adipocytes, associated with predipocytes, sympathetic nerve endings, vascular structures, and different types of inflammatory cells. In this review, we summarize the current knowledge about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 79 publications
0
23
0
5
Order By: Relevance
“…PRAT and accumulation of fatty acids in renal parenchyma cause the damage of tubulointerstitial tissue, proximal tubular epithelial cells, and endothelial cells [ 46 ]. Non-esterified fatty-acid (NEFA) accumulation leads to insulin resistance and apoptosis of podocytes which cannot regenerate [ 39 , 47 , 48 ]. Insulin resistance and hyperinsulinemia lead to activation of the sympathetic nervous system, which was confirmed by an increase in the concentration of catecholamines, and contributes to the occurrence of vasoconstriction [ 49 ].…”
Section: Obesity and Chronic Kidney Diseasementioning
confidence: 99%
“…PRAT and accumulation of fatty acids in renal parenchyma cause the damage of tubulointerstitial tissue, proximal tubular epithelial cells, and endothelial cells [ 46 ]. Non-esterified fatty-acid (NEFA) accumulation leads to insulin resistance and apoptosis of podocytes which cannot regenerate [ 39 , 47 , 48 ]. Insulin resistance and hyperinsulinemia lead to activation of the sympathetic nervous system, which was confirmed by an increase in the concentration of catecholamines, and contributes to the occurrence of vasoconstriction [ 49 ].…”
Section: Obesity and Chronic Kidney Diseasementioning
confidence: 99%
“…In fifty‐one patients with type 2 diabetes, renal sinus fat was negatively correlated with GFR and effective renal plasma flow and positively correlated with effective renal vascular resistance and mean arterial pressure mellitus after adjustments for body mass index, visceral adipose tissue and gender 100 . Perirenal adipose tissue has been linked to carotid intima–media thickness, vascular calcifications, visceral adiposity, hypertension and number of medications used in the treatment of hypertension, atherosclerosis, cardiovascular events, microalbuminuria and progression of chronic kidney disease in multiple large‐scale studies 63,101–107 . Although most studies, especially the cross‐sectional studies, do not consider perirenal fat thickness or renal sinus fat as an individual risk factor for the development of CKD, a few studies demonstrate that both are individual risk factors independent from other traditional risk factors.…”
Section: Fatty Kidney and Kidney And Cardiovascular Diseasementioning
confidence: 99%
“…In human embryos, PRAT-derived adipocyte progenitors differentiated in vitro exhibit similar features of BAT including PRDM16 and UCP1 expression, as well as a comparable mitochondrion copy number, gene expression patterns, and oxygen consumption rates ( 22 ). In newborns, PRAT predominantly consists of brown adipocytes with a thin layer of WAT, which exhibit an age-dependent, progressive regression, such that adult PRAT appears to be predominantly white with dispersed pockets of multilocular adipocytes ( 23 , 24 ). However, recent studies have shown that adult PRAT comprises spatially-distinct populations of dormant unilocular and multilocular UCP1-expressing adipocytes ( 21 , 24 26 ).…”
Section: Perirenal Adipose Tissue: Anatomy Histology and Originsmentioning
confidence: 99%